THEORETICAL FOUNDATIONS OF EFFECTIVE FAMILY COLLABORATION IN DEVELOPING CHILDREN’S READING CULTURE IN PRESCHOOL EDUCATION - Jumanova Fotima Uralovna; Allaberganova Munisa Begimboy qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The development of a reading culture in preschool children is fundamental to their overall cognitive and linguistic growth. This study examines the theoretical foundations of effective family collaboration in fostering children’s book reading habits within preschool education. Drawing on socio-cultural, ecological, and family systems theories, the research highlights the critical role of active family engagement in enhancing early literacy skills and motivation. Through a systematic review of literature, the paper identifies key strategies for establishing productive partnerships between families and educators. The findings emphasize the need for culturally responsive, inclusive, and communicative approaches to support diverse family contexts. Ultimately, strengthening family-preschool collaboration creates a supportive environment that nurtures children’s emergent reading culture, laying a foundation for lifelong learning and academic success.